Carbonyl reduction pathways in drug metabolism - Malátková, Petra; Wsól, Vladimír (Drug metabolism reviews, 2014)
The understanding of drug biotransformation is an important medical topic. The oxidative pathways that involve CYPs have been extensively studied in drug metabolism in contrast to the reductive pathways. This review focuses on drugs that have been reported to be reduced at the carbonyl group in vivo. Although the carbonyl reduction of these drugs is well known, our understanding of the carbonyl reducing enzymes (CRE) that perform these reactions is limited. We have summarized the published data in order to thoroughly describe the reductive metabolism of the selected drugs and to demonstrate the role of carbonyl reduction in the context of their overall metabolism. The number of drugs recognized as substrates for CREs has increased considerably in recent years. Moreover, the importance of carbonyl reduction in the overall metabolism of these drugs is often surprisingly high. Because only limited information is available about the CREs responsible for these reactions, additional research is needed to improve our understanding of the metabolism of drugs undergoing carbonyl reduction. Carbonyl reduction should be investigated during drug development because it can either positively or negatively influence drug efficacy.
Keywords: Oxidation-Reduction; Humans; Inactivation, Metabolic; oxidace-redukce; metabolická inaktivace; biotransformace; lidé; Alcohol Oxidoreductases; Biotransformation; Animals; alkoholoxidoreduktasy; zvířata